INTELLIGIBILITY OF THE KAZAKH SPEECH WHEN IT'S PROTECTED WITH COMBINED MASKING SIGNALS - Y. N. Seitkulov; S. N. Boranbayev; H. V. Davydau; A. V. Patapovich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2020)
The article is devoted to assessing the intelligibility of the Kazakh speech when it's masked by combined signals, including «white» noise and speech-like signals. The phonetics features of the Kazakh language have been considered taking into account the law of syngarmonism and the spectrum differences of speech in the Kazakh language and speech in the Russian language. A technique for assessing the intelligibility of the Kazakh speech when it's masked by «white» noise and speech-like signals is proposed. The aim of the work is to analyze well-known methods for speech intelligibility assessing and applying these methods to assess speech intelligibility in the Kazakh language, taking into account masking by its combined signals. Due to the fact that the use of the articulation method of assessing intelligibility for the Kazakh speech requires a dependence of intelligibility on the articulation index for this particular language (the application for the Kazakh language has not been experimentally tested), the use of the formant approach to speech intelligibility assessing will be examined in more detail. The curried out experimental studies of the spectral density of speech in the Kazakh language made it possible to obtain it's approximate dependence on the frequency and take into account the phonetic features of the Kazakh speech when assessing the security of the speech information using the formant method.